Effect of L-Ascorbyl-2-Phosphate Magnesium as a Vitamin C Source in Different Doses on Growth of Patin Pangasius Hypophthalmus Fingerlings - Jusadi, D.; Dewantara, B.A.; Mokoginta, I. (Jurnal Akuakultur Indonesia, 2006)
This study was aimed to determine optimum dose of L-Ascorbyl-2-Phosphate Magnesium in the diet of patin, Pangasius hypophthalmus fingerlings.  Five isoprotein and isocaloric diets containing different dose of L-Ascorbyl-2-Phosphate Magnesium, i.e. 0, 25, 75 and 100 mg/kg diet were used in this experiment.  Fish with an average size of 5.00±0.11 g were maintained at a density of 15 fish per aquarium.  Fish were fed three times a day at satiation, for 40 days.  The results of study shows that vitamin C content in fish body increased as the vitamin C level of the diet increased.  Similar pattern to vitamin C content was also found in protein retention, lipid retention, daily growth rate, and feed efficiency (p< 0.05).  Thus, it can  be concluded that the most optimum dose of L-Ascorbyl-2-Phosphate Magnesium as vitamin C source for patin fingerlings in this experiment was 100 mg Vit C/kg diet. Higher dose of L-Ascorbyl-2-Phosphate Magnesium than 100 mg/kg diet however need to be further verified. Keywords: vitamin C, patin, Pangasius hypophthalmus.   ABSTRAK Penelitian ini bertujuan untuk menentukan kadar optimum L-Ascorbyl-2-Phosphate Magnesium dalam pakan ikan patin, Pangasius hypophthalmus ukuran sejari. Lima macam pakan isoprotein dan isokalori mempunyai kandungan L-Ascorbyl-2-Phosphate Magnesium berbeda, berturut-turut 0, 25, 50, 75 dan 100 mg/kg pakan telah digunakan dalam penelitian ini. Benih berukuran rata-rata 5,00±0,11 g dipelihara dalam akuarium dengan kepadatan 15 ekor per akuarium. Ikan diberi pakan tiga kali sehari, secara at satiation, selama 40 hari. Hasil penelitian menunjukkan bahwa kadar vitamin C tubuh meningkat sejalan dengan kadar vitamin C pakan. Demikian pula retensi protein, retensi lemak laju pertumbuhan harian, efisiensi pakan mengikuti pola yang sama seperti kandungan vitamin C tubuh (p